2000
DOI: 10.1149/1.1393429
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Corrosion of Zinc in the Presence of NaCl The Influence of Carbon Dioxide and Temperature

Abstract: The atmospheric corrosion of zinc has been studied at 4, 22, and 38°C. The samples were exposed to synthetic air with careful control of CO2 concentration, relative humidity, and flow conditions. The relative humidity was 95%, and the concentrations of CO2 were <1 and 350 ppm, respectively. Sodium chloride was added before the exposures (0, 14, and 70 μnormalg/cm2 ). Mass gain and metal loss results are reported. As expected, NaCl is corrosive toward zinc, giving rise to heavy pitting. In the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 11 publications
8
57
0
1
Order By: Relevance
“…The atmospheric corrosion of zinc in the presence of NaCl and CO 2 is approximatively independent of temperature. The presence of CO 2 slows down NaCl-induced corrosion at 22 and 38 C (Lindström et al, 2000). In the presence of NaCl particles, similar corrosion rate was found after exposure to pure humid air or humid air containing gaseous pollutants SO 2 , NO 2 , O 3 , and NO 2 þO 3 (Chen, 2005).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The atmospheric corrosion of zinc in the presence of NaCl and CO 2 is approximatively independent of temperature. The presence of CO 2 slows down NaCl-induced corrosion at 22 and 38 C (Lindström et al, 2000). In the presence of NaCl particles, similar corrosion rate was found after exposure to pure humid air or humid air containing gaseous pollutants SO 2 , NO 2 , O 3 , and NO 2 þO 3 (Chen, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…With the amount of NaCl particles on copper surface lower than 15 mg/cm 2 , higher corrosion rate was found with <1 ppm CO 2 than with 350 ppm CO 2 (ambient level); but with higher amount of NaCl (>15 mg/cm 2 ), the corrosion was higher with 350 ppm CO 2 (Chen, 2005). It has been shown that CO 2 strongly influenced NaCl-induced atmospheric corrosion of zinc, aluminium, and magnesium, with a decreasing corrosion rate in the presence of ambient levels of CO 2 ( Lindström et al, 2000( Lindström et al, , 2002. CO 2 concentration inside the tunnel is higher than the ambient value.…”
Section: Interpretation Of the Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure 11, the main elements are Zn, C and O. Based on previous studies [8][9][10], the corrosive mechanism is proposed for galvanized steel under different air atmosphere. Firstly, zinc (Zn) reacts with oxygen (O) to form ZnO, which will further transform into Zn(OH) 2 under a certain humidity.…”
Section: Polarization Curve Measurementmentioning
confidence: 99%
“…On a time scale it usually reaches and almost constant level [7]. High corrosion rates can be included by high concentrations of air pollutants such as SO 2 , NO 2 , and O 2 [8][9][10], low rain pH [11], low degrees of surface inclinations in the prevailing wind direction [12], and corrosion rate is always lower in rural areas than in urban and marine environment [6].…”
Section: Introductionmentioning
confidence: 99%